FNDC5 relates to skeletal muscle IGF-I and mitochondrial function and gene expression in obese men with reduced growth hormone. (February 2016) - Srinivasa, Suman; Suresh, Caroline; Mottla, Jay; Hamarneh, Sulaiman R.; Irazoqui, Javier E.; Frontera, Walter; Torriani, Martin; Stanley, Takara; Makimura, Hideo
Abstract: Objective: To investigate the relationship of skeletal muscle FNDC5 mRNA expression and circulating irisin to the GH/IGF-I axis and to skeletal muscle mitochondrial function and mitochondria-related gene expression in obese men. Design: Fifteen abdominally obese men with reduced growth hormone received 12 weeks of recombinant human GH (rhGH). Before and after treatment, they underwent 31 P-magnetic resonance spectroscopy to evaluate phosphocreatine (PCr) recovery as a measure of mitochondrial function and skeletal muscle biopsy to assess expression of mitochondrial-related genes. Serum irisin and IGF-I and skeletal muscle FNDC5 and IGF-I mRNA were measured. Results: At baseline, skeletal muscle FNDC5 mRNA was significantly and positively associated with IGF-I mRNA (ρ = 0.81, P = 0.005) and rate of PCr recovery (ρ = 0.79, P = 0.006). Similar relationships of circulating irisin to IGF-I mRNA (ρ = 0.63, P = 0.05) and rate of PCr recovery (ρ = 0.48, P = 0.08) were demonstrated, but were not as robust as those with muscle FNDC5 expression. Both serum irisin and skeletal muscle FNDC5 mRNA were significantly associated with PPARγ (ρ = 0.73, P = 0.02 and ρ = 0.85, P = 0.002), respectively. In addition, FNDC5 mRNA was correlated with skeletal muscle PGC-1α (ρ = 0.68, P = 0.03), NRF1 (ρ = 0.66, P = 0.04) and TFAM (ρ = 0.79, P = 0.007) mRNA. Neither serum irisin nor muscle mRNA expression of FNDC5 changed with rhGH treatment. Conclusion: These novel data in skeletal muscle demonstrate that local expression of FNDC5 is associated with mRNA expression of IGF-I and mitochondrial function and mitochondria-related gene expression in obese subjects with reduced growth hormone and suggest a potential role for FNDC5 acting locally in muscle in a low GH state. Further studies are needed to clarify the relationship between the GH/IGF-I axis and irisin. Highlights: FNDC5 mRNA and circulating irisin are associated with mRNA expression of IGF-I. FNDC5 mRNA correlates with the rate of phosphocreatine recovery after exercise. FNDC5 mRNA and irisin do not change after 12 weeks of growth hormone replacement.